Implementing international humanitarian law in the Caribbean (International Committee of the Red Cross GenevaCH, 2005)
Provides relevant model laws that can be used as a guide to CARICOM governments and other stakeholders in their efforts to proceed with international humanitarian law implementation.
Keywords: INTERNATIONAL LAW